2006
DOI: 10.1007/s00213-006-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired recognition of fear facial expressions in 5-HTTLPR S-polymorphism carriers following tryptophan depletion

Abstract: The effects of acute tryptophan depletion on the processing of emotional expressions varies as a function of genotype at the 5-HTTLPR. Depletion impairs the recognition of fear in s carriers but not ll homozygotes. This finding reinforces the importance of considering genotype when assessing the behavioral effects of pharmacologic modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
5
52
3
1
Order By: Relevance
“…Of these, ten (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) evaluated the effects of acute manipulation of the 5-HT system. Three studies (25)(26)(27) evaluated the effects of sub-chronic or chronic treatment with 5-HT probes; one of them also included a noradrenergic drug (25).…”
Section: Review Protocolmentioning
confidence: 99%
“…Of these, ten (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) evaluated the effects of acute manipulation of the 5-HT system. Three studies (25)(26)(27) evaluated the effects of sub-chronic or chronic treatment with 5-HT probes; one of them also included a noradrenergic drug (25).…”
Section: Review Protocolmentioning
confidence: 99%
“…Several studies have shown that 5-HTTLPR genotype can influence behavioral responses to ATD (Marsh et al 2006;Neumeister et al 2006;Roiser et al 2006;Walderhaug et al 2007). As wildtype (SERT +/+ ), heterozygous (SERT +/− ), and knockout (SERT −/− ) rats exhibit large differences in central 5-HT neurotransmission, the impact of ATD may vary accordingly in these rats.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, one might interpret our data as indicating that acute variations in the functionality of the serotonergic system, indeed, only modulate positive emotionality in those subjects who are genetically predisposed. Underpinning this, there is evidence that 5-HTTLPR-genotype moderates the effects of, e.g., acute tryptophan depletion on mood and behavior (Marsh et al, 2006;Neumeister et al, 2006;Markus and Firk, 2009;Markus and De Raedt, 2011), pointing to a higher vulnerability to alterations in the serotonergic neurotransmission in ss-homozygotes.…”
Section: Discussionmentioning
confidence: 98%